Does the posterolateral bundle influence rotational movement more than the anteromedial bundle in anterior cruciate ligament reconstruction?: a clinical study - Komzák, M; Hart, R; Okál, F; Safi, A (The Journal of bone and joint surgery. British volume, 2012)
The biomechanical function of the anteromedial (AM) and posterolateral (PL) bundles of the anterior cruciate ligament (ACL) remains controversial. Some studies report that the AM bundle stabilises the knee joint in anteroposterior (AP) translation and rotational movement (both internal and external) to the same extent as the PL bundle. Others conclude that the PL bundle is more important than the AM in controlling rotational movement. The objective of this randomised cohort study involving 60 patients (39 men and 21 women) with a mean age of 32.9 years (18 to 53) was to evaluate the function of the AM and the PL bundles of the ACL in both AP and rotational movements of the knee joint after single-bundle and double-bundle ACL reconstruction using a computer navigation system. In the double-bundle group the patients were also randomised to have the AM or the PL bundle tensioned first, with knee laxity measured after each stage of reconstruction. All patients had isolated complete ACL tears, and the presence of a meniscal injury was the only supplementary pathology permitted for inclusion in the trial. The KT-1000 arthrometer was used to apply a constant load to evaluate the AP translation and the rolimeter was used to apply a constant rotational force. For the single-bundle group deviation was measured before and after ACL reconstruction. In the double-bundle group deviation was measured for the ACL-deficient, AM- or PL-reconstructed first conditions and for the total reconstruction. We found that the AM bundle in the double-bundle group controlled rotation as much as the single-bundle technique, and to a greater extent than the PL bundle in the double-bundle technique. The double-bundle technique increases AP translation and rotational stability in internal rotation more than the single-bundle technique.
Keywords: lidé středního věku; rotace; ligamentum cruciatum anterius; Rotation; Stereotaxic Techniques; Humans; Middle Aged; Anterior Cruciate Ligament; Knee Joint; Female; Anterior Cruciate Ligament Reconstruction; mladiství; poranění kolena; ženské pohlaví; kolenní kloub; mladý dospělý; Adult; Young Adult; stereotaktické techniky; Adolescent; dospělí; rekonstrukce předního zkříženého vazu; lidé; Knee Injuries